Pottery firing temperatures: A new method for determining the firing temperature of ceramics and burnt clay - Rasmussen, Kaare Lund (2012)
A new method for determining the maximum ﬁring temperature of ceramics and burnt clay is presented. The technique relies on measuring the magnetic susceptibility on a step-wise re-ﬁred sample. The validity of the method has been tested by determining ﬁring temperatures of two sets of clay samples ﬁred at temperatures ranging from 400 to 1000 C. Aliquots of the same samples have been studied petrographically by optical microscopy on thin sections and analyzed by powder X-ray diffraction in order to monitor structural and mineralogical changes as a function of temperature. The method is demonstrated on samples from four geographically widely different sites and it is applied to a larger set of ceramics of Late (ca. AD 900eAD 1450) and Inca (ca. AD 1480eAD 1532) periods from the Northwestern Argentine region, dating to a limited period of time prior to the fall of the Inca Empire. The method is shown to be a powerful tool in revealing archaeological information about the change in ﬁring technologies in the pre-Hispanic societies in the Andean area through time.